2019
DOI: 10.1177/1744259119867461
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigations of wooden beam ends in masonry with interior insulation: Measured data in real-scale experimental walls exposed to semi-continental climatic conditions

Abstract: This article deals with the hygrothermal performance of wooden beam ends embedded in brick masonry walls. The real-scale experiment involving three interior insulation systems with different water vapor resistances and different treatments of joist pockets was monitored for three consecutive years. The moisture load of test walls was controlled during the experiment. First, humidity of indoor air was increased in the cold season (2016–2017). Then, an artificial short-time intensive rain event brought liquid wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
0
4
1
Order By: Relevance
“…A comparison between the diffusion-tight systems showed less critical RH levels in the Phenolic foam compared with the MW + VB, which was probably due to increased moisture accumulation in the MW + VB system caused by the increased diffusion resistance. These results do not support the findings in Kopecky´et al (2019) and Vereecken and Roels (2019), where more critical RH levels were observed for the highly diffusionopen systems compared with the more diffusion-tight, while these studies did not account for WDR on the exterior surfaces or were to some extent protected against WDR. In addition, the authors also found reduced RH levels in the beam ends by reducing the flow of indoor air by sealing off the beam pockets with PUR foam or tape, where the diffusion-tight systems also showed reduced RH levels compared with the diffusion-open.…”
Section: System Comparison (Non-hydrophobised Walls)contrasting
confidence: 96%
“…A comparison between the diffusion-tight systems showed less critical RH levels in the Phenolic foam compared with the MW + VB, which was probably due to increased moisture accumulation in the MW + VB system caused by the increased diffusion resistance. These results do not support the findings in Kopecky´et al (2019) and Vereecken and Roels (2019), where more critical RH levels were observed for the highly diffusionopen systems compared with the more diffusion-tight, while these studies did not account for WDR on the exterior surfaces or were to some extent protected against WDR. In addition, the authors also found reduced RH levels in the beam ends by reducing the flow of indoor air by sealing off the beam pockets with PUR foam or tape, where the diffusion-tight systems also showed reduced RH levels compared with the diffusion-open.…”
Section: System Comparison (Non-hydrophobised Walls)contrasting
confidence: 96%
“…Fungi colonization, mold growth, and wood decay might then appear, especially when the relative humidity is kept above 81% and 90%, respectively [53]. This was also approved by Kopecky et al [54] who revealed small spots of mold on the beam during an experimental investigation even when exposed to mild weather conditions.…”
Section: Resultsmentioning
confidence: 85%
“…Even if the interior thermal insulation contributes to increased hygrothermal straining, the favorable hygrothermal patterns are met only occasionally as high temperatures are reached mostly in summer periods, while high relative humidity in the winter ones. This might be the reason why other researchers do not mention the problem of biofilms growth on exterior surfaces at all and rather focus on different specifics of interior thermal insulation systems [12,52,54].…”
Section: Resultsmentioning
confidence: 99%
“…To prevent convective moisture transport, as discussed in (Vereecken and Roels, 2018), the gap between the wooden beam and the insulation system was sprayed up with flexible PUR-foam and the connection with the interior surface was sealed with an airtight tape. After all, also in hygrothermal studies including a wind-driven rain exposure (Kopecký et al, 2019) an airtight sealing of the beam junction has been put forward.…”
Section: Test Wallsmentioning
confidence: 99%